“It Feels Like a Performance When I Teach Online”: Autoethnography of Tensions in Teacher Identity - Daron Benjamin Loo (Universidad Nacional de Colombia (Sede Bogotá), 2023)
This autoethnographic study examined the tensions affecting the identity of a teacher in charge of an online English academic writing module during the COVID-19 pandemic. Reflections written over one academic year were examined using performativity as an analytical lens. The analysis identified three types of tensions: performing for proximity, performing to meet the institution’s and student’s expectations, and continuously changing performances. These tensions highlight the teacher’s performativity when using technology, which ultimately configured his teacher identity. From these tensions, the paradox of technology may be observed. Specifically, tools supposedly productive for an online class may not necessarily be well received by students and may burden the teacher.